2013
DOI: 10.1073/pnas.1221105110
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal accumulation and recycling of glycoproteins visualized in Niemann–Pick type C cells using the chemical reporter strategy

Abstract: Niemann-Pick type C (NPC) disease is characterized by impaired cholesterol efflux from late endosomes and lysosomes and secondary accumulation of lipids. Although impaired trafficking of individual glycoproteins and glycolipids has been noted in NPC cells and other storage disorders, there is currently no effective way to monitor their localization and movement en masse. Using a chemical reporter strategy in combination with pharmacologic treatments, we demonstrate a disease-specific and previously unrecognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…Next, HEL cells were either incubated with Ac 4 ManNAz for 24 h, or SEEL labeled with rat ST6Gal1 or human ST3Gal1 in the presence of CMP-Neu5Ac9N 3 followed by treatment with S-DIBO for biotinylation (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, HEL cells were either incubated with Ac 4 ManNAz for 24 h, or SEEL labeled with rat ST6Gal1 or human ST3Gal1 in the presence of CMP-Neu5Ac9N 3 followed by treatment with S-DIBO for biotinylation (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…CMP-Neu5Ac9N 3 , S-DIBO-Biotin, Ac 4 ManNAc, and Ac 4 ManNAz were synthesized as previously described (16,30). Vibrio cholerae neuraminidase (type II) was purchased from Sigma Aldrich (N6514).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been recently shown that modulation of glycosylation of APP, a key protein in the pathogenesis of AD, may represent a potential target for AD therapy (18). It has been previously shown that glycoproteins accumulate in NPC model (19), and that blocking the O-linked glycosylation lowers cholesterol levels and increases the number of lysosomes (20), thus rescuing the NPC cellular defects. In the present work, we studied N-glycosylation profile of the lysosomal membrane proteins in NPC1-null cells vs. wt-cells.…”
Section: Introductionmentioning
confidence: 99%